Ciri-ciri konstruksi ergatif dalam bahasa Melayu (Jurnal Bahasa, 2008)
The meanings of voices of verbs in the Malay language have been taught in a dichotomy between active and passive, being based only formally on the framework of modern European languages. As a result, less attention has been paid on the linguistic facts that have existed since the era of classical Malay, in the arena of language education. We often find, for example, passive sentences of Malay that bear notional active meaning of "A acts upon B " in the syntactic structure of a sentence. This opposition of active passive voices needs to be examined by observing the differences of voices between Malay and European languages. In this respect, an idea of distinguishing PURE PASSIVE (zuiver passief)from AGENTIVE PASSIVE (subjectiefpassief)proposed by Hollander (1856) leads indirectly to the finding of an idea of ERGATIVE CONSTRUCTION in the study of the traditionally so-called "passive sentence" of Malay. By using this new idea, the problem of nominal cases of Malay could also be discussed in its own framework of sentence. This article will reexamine the functions of voices of verbs in Malay, being based on the linguistic facts and the findings that were produced since the 19th century in the history of the study of Malay grammar.